2012
DOI: 10.1103/physrevb.86.125415
|View full text |Cite
|
Sign up to set email alerts
|

Quantum oscillations of spin polarization in a GaAs/AlGaAs double quantum well

Abstract: We employ the circular polarization-resolved magneto-photoluminescence technique to probe the spin character of electron and hole states in a GaAs/AlGaAs strongly coupled double quantum well system. The photoluminescence intensities of the lines associated with symmetric and antisymmetric electron states present clear out-of-phase oscillations between integer values of the filling factor ν and are caused by magnetic field induced changes in the population of occupied Landau levels near to the Fermi level of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Figures 3(c) and (d) present, respectively, the odd parity °Pz (solid green curves) and the even parity P z e (dashed orange curves) for states A and B of the valence band when θ = °0 . Such results show that spin character and even parity are well defined for states A and B when θ = °0 , as already observed in [5,22]. In fact, state A is a pure spin-down HH state ⟩ ⟩ ( )…”
Section: Resultssupporting
confidence: 78%
“…Figures 3(c) and (d) present, respectively, the odd parity °Pz (solid green curves) and the even parity P z e (dashed orange curves) for states A and B of the valence band when θ = °0 . Such results show that spin character and even parity are well defined for states A and B when θ = °0 , as already observed in [5,22]. In fact, state A is a pure spin-down HH state ⟩ ⟩ ( )…”
Section: Resultssupporting
confidence: 78%
“…The first phenomenon has been reported for some systems 36 and it is under investigation, while the second one can be attributed to the spin dynamics during carrier relaxation at the conduction band. 37 We have observed that the polarization degrees for the N-2containing samples are slightly higher than for N-free samples and the spin-dependent effects are stronger for wider QWs for both systems. Remark that under higher magnetic fields, the spin polarization degree remains within the range of [À20, À10%], regardless of the structural parameters of the QW.…”
Section: Resultsmentioning
confidence: 67%
“…Therefore, they cannot be attributed to the magnetic-field-induced variations in the occupied density of states of the Landau levels nearest the Fermi energy as detected in Ref. [45]. We assign the PL intensity maxima found in the tilted magnetic field to the collapses of the tunneling gaps shown in the magnetoresistance plot by open gray circles.…”
Section: Resultsmentioning
confidence: 67%